Differences on prosaccade task in skilled and less skilled female adolescent soccer players - Zhou, J. (Frontiers in Psychology, 2021)
Although the relationship between cognitive processes and saccadic eye movements has been outlined, the relationship between specific cognitive processes underlying saccadic eye movements and skill level of soccer players remains unclear. Present study used the prosaccade task as a tool to investigate the difference in saccadic eye movements in skilled and less skilled Chinese female adolescent soccer players. Fifty-six healthy female adolescent soccer players (range: 14-18years, mean age: 16.5years) from Fujian Youth Football Training Base (Fujian Province, China) took part in the experiment. In the prosaccade task, participants were instructed to fixate at the cross at the center of the screen as long as the target appeared peripherally. They were told to saccade to the target as quickly and accurately as possible once it appeared. The results indicated that skilled soccer players exhibited shorter saccade latency (p=0.031), decreased variability of saccade latency (p=0.013), and higher spatial accuracy of saccade (p=0.032) than their less skilled counterparts. The shorter saccade latency and decreased variability of saccade latency may imply that the attentional system of skilled soccer player is superior which leads to smaller attention fluctuation and less attentional lapse. Additionally, higher spatial accuracy of saccade may imply potential structural differences in brain underlying saccadic eye movement between skilled and less skilled soccer players. More importantly, the results of the present study demonstrated that soccer players` cognitive capacities vary as a function of their skill levels. The limitations of the present study and future directions of research were discussed.